Formatting and paratextual elements in Croatian books printed in Divald’s print house by 1800 (Libellarium: journal for research in the field of information and related sciences, 2013)
The aim of the paper is to investigate formatting and use of paratextual elements in books printed in Croatian in Ivan Martin Divald’s print house in Osijek from 1779 to the end of the 18th century. The corpus included Divald’s books from the Essekiana Collection of the library in The Museum of Slavonia in Osijek.The research was conducted by correlating the format, genre, presence or absence of paratextual elements and formatting, looking in particular at paragraph and chapter organization and use of notes. The research results show that a standardized format as well as formatting was used (textual organization, use of notes), but that the paratextual elements were not used in a systematic fashion.By focusing on a shorter time-span and one print house only, we excluded the possible influence of different print styles and practices, which made the formatting independent of different designer approaches. This is also the major limitation of this research, as a small corpus does not allow for generalizations.
Keywords: formatting; paratextual elements; genres; book formats; book history; Ivan Martin Divald; Osijek